Strategi Komunikasi Crowdfunding Melalui Media Sosial (Studi Kasus Strategi Komunikasi Crowdfunding "Upcycling Project Untuk Anak Putus Sekolah" Melalui Media Sosial Wujudkan.com) - Ariesta, Ovinandya, Palupi, M.A (2016)
Crowdfunding is one alternative funding that can be implemented by businesses minimal capital made through the internet. Kayonara is one of the fundraisers with a project called "Upcycling project for school dropouts" were made through wujudkan.com platform. This study investigates the how communication strategy undertaken by Kayonara doing crowdfunding through social media wujudkan.com. This research is a case study with a qualitative approach. Collecting data using the techniques of interview, observation and documentation. While informants selected using snowball sampling technique. In this study, the validity of the source is obtained using triangulation techniques. The result showed that the communication from Kayonara goal is to raise funds through wujudkan.com. For segmenting the target audience is primarily students and the middle class. Preparation of messages that do both side issue and delivered through articles and videos. Selection of media use blogs wujudkan.com. and the role of communicators do is bring the gospel to the donors about the development projects carried out.